Research on dual process theory based telecom augmented cognition - Xiaoxing LIAN; Yong SONG; Jun ZHU; Shuling WANG; Xiaozhou YE; Ye OUYANG (Dianxin kexue)
Incorporating the current works in augmented large language models (LLM), a dual process theory based telecom augmented cognition architecture (TACA) was proposed.This architecture addressed challenges faced by LLM in the field of telecom, such as lack of domain-specific knowledge and limited reasoning capabilities.It aims to enhance cognitive reasoning, knowledge integration, tooling, and autonomous decision-execution capabilities for complex telco-scenarios.Technical application references for different telco-scenarios were provided, and the effectiveness and feasibility of the augmented cognition solution were preliminarily validated in addressing complex problems through experiments.The proposed TACA can serve as a future reference architecture for the application of LLMs in the telecom industry.